Standardizzazione, automazione e responsabilità medica. Dalle recenti riforme alla definizione di un modello d’imputazione solidaristico e liberale (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
In the first part of the article (§ 1-6), the author deals with the debate about the limits of criminal liability for negligent medical malpractice in a global context characterized by the standardization of clinical practices. The critical consideration of the recent legal reforms in Italy, as well as the prevalent models defended by criminal law scholars, allows the configuration of a paradigm of imputation capable of combining the interests of patients with those of health professionals. In the last part (§ 7-8), the author considers how the same “balanced” –liberal as well as solidaristic– criterion could allow regulating medical liability for adopting indications provided by Artificial Intelligence systems. The conclusions (§ 9) emphasise how standardisation and automation processes find an insurmountable obstacle in the defence of pluralism, autonomy and the ethics of responsibility.
Keywords: Standardisation; Artificial Intelligence; Autonomy; Medical Malpractice; Criminal Negligence